Self-reported violations, errors and lapses for older drivers: Measuring the change in frequency of aberrant driving behaviours across five time-points. (February 2019) - Koppel, Sjaan; Stephens, Amanda N.; Bédard, Michel; Charlton, Judith L.; Darzins, Peteris; Stefano, Marilyn Di; Gagnon, Sylvain; Gélinas, Isabelle; Hua, Phuong; MacLeay, Lynn; Man-Son-Hing, Malcolm; Mazer, Barbara; et al.
Highlights: A 21-item, three-factor version of the DBQ was confirmed in a sample of Canadian older drivers. Older drivers' responses to this version of the DBQ were stable across four years. Older drivers' errors, violations and lapses remained similar across four years. Abstract: The current study aimed to: 1. to confirm the 21-item, three-factor Driver Behaviour Questionnaire (DBQ) structure suggested by Koppel et al. (2018) within an independent sample of Canadian older drivers; 2. to examine whether the structure of the DBQ remained stable over a four-year period; 3. to conduct a latent growth analysis to determine whether older drivers' DBQ scores changed across time. Five hundred and sixty Canadian older drivers (males = 61.3%) from the Candrive/Ozcandrive longitudinal study completed the DBQ yearly for four years across five time-points that were approximately 12 months apart. In Year 1, the average age of the older drivers was 76.0 years (SD = 4.5 years; Range = 70–92 years). Findings from the study support the 21-item, three-factor DBQ structure suggested by Koppel and colleagues for an Australian sample of older drivers as being acceptable in an independent sample of Canadian older drivers. In addition, Canadian older drivers' responses to this version of the DBQ were stable across the five time-points. More specifically, there was very little change in older drivers' self-reported violations, and no significant change for self-reported errors or lapses. The findings from the current study add further support for this version of the DBQ as being a suitable tool for examining self-reported aberrant driving behaviours in older drivers. Future research should investigate the relationship between older drivers' self-reported aberrant driving behaviours and their performance on functional measures, their responses to other driving-related abilities and practice scales and/or questionnaires, as well their usual (or naturalistic) driving practices and/or performance on on-road driving tasks.